On Free Pseudo-Product Fundamental Graded Lie Algebras - Yatsui, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
In this paper we first state the classification of the prolongations of complex free fundamental graded Lie algebras. Next we introduce the notion of free pseudo-product fundamental graded Lie algebras and study the prolongations of complex free pseudo-product fundamental graded Lie algebras. Furthermore we investigate the automorphism group of the prolongation of complex free pseudo-product fundamental graded Lie algebras.